Enhanced sulfonamides removal via microalgae-bacteria consortium via co-substrate supplementation. (August 2022) - Wang, Yue; Li, Jinghua; Lei, Yao; Cui, Rong; Liang, Aiping; Li, Xiaoqiang; Kit Leong, Yoong; Chang, Jo-Shu
Graphical abstract: Highlights: Supply of co-substrate to algae-bacteria consortia enhances antibiotics degradation. Co-substrate improved SDZ degradation more significantly than SMX degradation. Co-substrate induced the secretion of microalgal EPS with high protein ratios. Supplementation of co-substrate could decrease peroxide damage to cells. The symbiotic bacterial diversities were analyzed by high throughput sequencing. Abstract: Both co-cultivation and co-substrate addition strategies have exhibited massive potential in microalgae-based antibiotic bioremediation. In this study, glucose and sodium acetate were employed as co-substrate in the cultivation of microalgae-bacteria consortium for enhanced sulfadiazine (SDZ) and sulfamethoxazole (SMX) removal. Glucose demonstrated a two-fold increase in biomass production with a maximum specific growth rate of 0.63 ± 0.01 d −1 compared with sodium acetate. The supplementation of co-substrate enhanced the degradation of SDZ significantly up to 703 ± 18% for sodium acetate and 290 ± 22% for glucose, but had almost no effect on SMX. The activities of antioxidant enzymes, including peroxidase, superoxide dismutase and catalase decreased with co-substrate supplementation. Chlorophyll a was associated with protection against sulfonamides and chlorophyll b might contribute to SDZ degradation. The addition of co-substrates influenced bacterial community structure greatly. Glucose enhanced the relative abundance of Proteobacteria, while sodium acetate improved the relative abundance of Bacteroidetes significantly.